2021
DOI: 10.1177/24705470211006855
|View full text |Cite
|
Sign up to set email alerts
|

Task-Modulated Brain Activity Predicts Antidepressant Responses of Prefrontal Repetitive Transcranial Magnetic Stimulation: A Randomized Sham-Control Study

Abstract: Background Prolonged intermittent theta-burst stimulation (piTBS) and repetitive transcranial magnetic stimulation (rTMS) are effective antidepressant interventions for major depressive disorder (MDD). Cognition-modulated frontal theta (frontalθ) activity had been identified to predict the antidepressant response to 10-Hz left prefrontal rTMS. However, whether this marker also predicts that of piTBS needs further investigation. Methods The present double-blind randomized trial recruited 105 patients with MDD w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Although the clinical outcomes from the subdataset of Li et al (2020) did not show a larger antidepressant effect in terms of percentage changes of HDRS for rTMS (30.19%) in comparison to the sham (14.75%) which may be due to the smaller effect size, the full dataset from Li et al (2020) has shown that piTBS and rTMS have a similar antidepressant effect which was significantly larger than sham. This finding was consistent with the results of our previous studies (Li et al, 2021) and similar to Blumberger et al (2018). In spite of the comparable treatment effect based on the two stimulating protocols, the underlying antidepressant physiological function of rTMS and piTBS might be different and might be represented by distinct patterns of changes in brain oscillations.…”
Section: Discussionsupporting
confidence: 94%
“…Although the clinical outcomes from the subdataset of Li et al (2020) did not show a larger antidepressant effect in terms of percentage changes of HDRS for rTMS (30.19%) in comparison to the sham (14.75%) which may be due to the smaller effect size, the full dataset from Li et al (2020) has shown that piTBS and rTMS have a similar antidepressant effect which was significantly larger than sham. This finding was consistent with the results of our previous studies (Li et al, 2021) and similar to Blumberger et al (2018). In spite of the comparable treatment effect based on the two stimulating protocols, the underlying antidepressant physiological function of rTMS and piTBS might be different and might be represented by distinct patterns of changes in brain oscillations.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, one study manipulated the increased frontal ACC theta by asking the participants to perform an rACC-engaging cognitive task between two resting EEG conditions before the rTMS treatment. The results show that the frontal theta activity after the cognitive task at the pre-treatment phase could predict the antidepressant response up to 89% within the area under the curve (AUC) of the receiver operating characteristic (ROC) ( 49 ); however, this index could not predict the antidepressant efficacy by delivering iTBS ( 50 ). Additionally, the lower relative theta power, which indicated the ratio of theta to total power, in frontal regions at the pre-treatment stage was found in responders than in non-responders, which could predict the antidepressant responses ( 39 , 51 ).…”
Section: Eeg and Depressionmentioning
confidence: 99%